Eastern Europe before transition: Exploring historical trade data on external economic relations in CESEE's command economies - Doris Hanzl-Weiss (The Vienna Institute for International Economic Studies (wiiw), 2024)
This paper revisits the external economic relations in the former command economies of Central, East and Southeast Europe (CESEE) by exploring historical trade data. It provides a descriptive analysis of foreign trade statistics, drawing on the newly introduced wiiw COMECON Dataset, which contains economic time series of the Council for Mutual Economic Assistance (CMEA or COMECON) countries from 1945 to 1994. While trade with the West was limited, the majority of trade took place among the CMEA members states, with the Soviet Union (USSR) serving as the most important partner. The USSR supplied energy and raw materials to its partners in exchange for manufactured products and other goods. However, when examining historical data from CESEE's command economies, it is important to consider the limitations of data and distinctive features of this economic system.
Keywords: 330; Command economies; Central; East and Southeast Europe; international trade; CMEA; COMECON; economic history; historical statistics